Pengaruh Promosi Online, Celebrity Endorser, dan Kelompok Referensi terhadap Keputusan Pembelian Diamond Mobile Legends di Kota Kupang: Peran Mediasi Gaya Hidup - Maru, Ignasia Natasya Taju; Goetha, Selfiana; Niha, Simon Sia (Journal of Innovation in Management, Accounting and Business, 2024)
This research discusses the decision to purchase diamonds in the Mobile Legend game in Indonesia, focusing on lifestyle, celebrity endorsers, referral groups, and online promotions. This game is in demand because of the variety of heroes, good graphics, small size, and easy access via smartphones. Diamonds are an important virtual currency in games that influence players' purchasing decisions. Diamond sales data from 2018 to 2022 showed a downward trend, especially in 2022 with a decline of 15.2%. Interviews with 30 players in Kupang City indicated that promotions with celebrity endorsers were not interesting because they were less attractive, rude, and irrelevant. The research used a survey of 112 respondents in Kupang City who had bought Mobile Legend diamonds, analyzed with SEM-PLS. The results showed that lifestyle, celebrity endorsers, and referral groups had a positive and significant effect on purchase decisions, while online promotions were not significant. This research contributes to the understanding of the factors that influence diamond purchase decisions in Mobile Legend and opens up opportunities for the exploration of more effective online promotion strategies.